The Method of Ensuring Equal Participation of Students During Group Work in the Crisis of the Covid-19 Pandemic - Ihor Romanyshyn; Svitlana Yatsiv; Yuliia Demchuk (Vasyl Stefanyk Precarpathian National University, 2023)
This study is a small-scale action research on the problem of EFL/ESL students' participation in group activities during the crisis of the COVID-19 pandemic. The main stages of the research were conducted in the academic year of 2020/21. The population of the study is twenty-eight Ukrainian secondary school students and three teachers. The research aims at designing a method for ensuring learner engagement in and equal contribution to the group project during distance learning. The methodological basis of this study is the theories of "The Model of Willingness to Communicate", "Collaborative Learning" and "Social Interdependence". The quantitative and qualitative data have been collected through the mixed-method approach, in particular via pedagogical observation, surveys (teacher interviews and student questionnaires), peer evaluation, and mathematical statistics (descriptive and frequency methods). The analysis of scientific pedagogical and psychological literature on student engagement during traditional (in-person) and distance (synchronous and asynchronous) learning, including the use of social networks in education (Viber, Zoom, etc.), helped to identify the main factors that affect learner engagement and equal participation in group activities, such as psychological (self-confidence, anxiety, shyness, and personality), group formation (group size, teacher/student-formed, and homogeneous/heterogeneous), monitoring (self, peer and teacher) and evaluation (peer and teacher). The results of this study demonstrate that the teacher greatly influences the success and equality of student participation in small-group activities. Identifying reasons for unequal participation in the target group of learners, considering students' personality traits and individual needs, and using appropriate planning, organizing and monitoring strategies are the key to their active engagement and effective group work. The results of this study could be used by researchers and practitioners working in the sectors of secondary and tertiary education.